ORGANIZATIONAL AND TECHNICAL CONTROL CONSTRUCTION PROJECTS IN THE AREA OF CITIZENS WITH QUALITY BOTTLED DRINKING WATER IS NOT - and and (Municipal economy of cities (Technical science), 2013)
Developed a managed organizational and technical system of "management of construction projects in the area of supply nefasovanoï drinking water from underground sources (CCU PX), based on which you can develop and manage specific unique projects as part of this system. It is proposed to use when creating a small and middle business enterprises with production, transportation and sale of high quality drinking water to the population nefasovanoï with underground Springs Road.